Strategi Dakwah Guru SMA Plus Negeri 17 Palembang dalam Membina Akhlak Siswa di Asrama Tahun Ajaran 2017/2018 - Hamidah Hamidah; Manalullaili Manalullaili; Alham Irvani (Program Studi Komunikasi dan Penyiaran Islam UIN Raden Fatah Palembang, 2017)
This research was conducted to explain and straighten about the view of the community on the image of boarding schools that are less good in some communities carried out in the cottage messagerenren Ar_Riyadh 13 Ulu Palembang.Karena as the development dzaman and the development of world of technology increasingly sophisticated, the parents began to smarter in choosing educational institutions for his son. However, there are some people who are not paying attention and give attention to their children so that the boarding school is suitable for their children so that the community indirectly assume that boarding school as a daycare and place of naughty children. Therefore the thesis that the researcher created entitled